Pengaruh Promosi dan Citra Produk/Brand Image Terhadap Keputusan Pembelian Pada Merk Nevada di Matahari Departement Store Malang Town Square - Amirullah, Fahad; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of promotion and product/brand image on purchasing decisions for the Nevada brand at Matahari Department Store Malang Town Square. Competition in the fashion industry requires companies to continuously innovate in marketing strategies, especially in terms of promotion and brand image. Effective promotion and a strong brand image can influence consumer purchasing decisions. This research uses a quantitative method by distributing questionnaires to 150 respondents who have purchased Nevada products. The analysis results show that both promotion and brand image have a positive and significant effect on consumer purchasing decisions. These findings indicate the importance of innovative promotional strategies and a good brand image in increasing consumer purchasing decisions in fashion products. Keywords : The Influence of Promotion and Product Image/Brand Image on Purchasing Decisions